Fashion : philosophy for everyone : thinking with style - Wolfendale, Jessica, 1973-; Kennett, Jeanette; Wiley InterScience (Online service) (Malden, MA : Wiley, 2011)
If you just can't decide what to wear, this enlightening guide will lead you through the diverse and sometimes contradictory aspects of fashion in a series of lively, entertaining and thoughtful essays from prominent philosophers and writers. A unique and enlightening insight into the underlying philosophy behind the power of fashion. Contributions address issues in fashion from a variety of viewpoints, including aesthetics, the nature of fashion and fashionability, ethics, gender and identity politics, and design.
Front Matter -- Introduction / Jessica Wolfendale, Jeanette Kennett -- Being Fashionable and being Cool. What Makes Something Fashionable? / Anya Farennikova, Jesse Prinz -- Fashion, Illusion, and Alienation / Nick Zangwill -- Tryhards, Fashion Victims, and Effortless Cool / Luke Russell -- Fashion, Style, and Design. The Aesthetics of Design / Andy Hamilton -- Share the Fantasy / Cynthia A Freeland -- Computational Couture / Ada Brunstein -- Fashion, Identity, and Freedom. Wearing your Values on your Sleeve / Daniel Yim -- Fashion and Sexual Identity, or why Recognition Matters / Samantha Brennan -- Slaves to Fashion? / Lauren Ashwell, Rae Langton -- Fashion Dolls and Feminism / Louise Collins -- Can we be Ethical . Sweatshops and Cynicism / Matthew F Pierlott -- Women Shopping and Women Sweatshopping / Lisa Cassidy -- A Taste for Fashion / Marguerite La Caze -- Notes on Contributors.
Keywords: Fashion -- Philosophy; Clothing and dress -- Philosophy; Electronic resource; Electronic resource